The Controversy of Psychophysical Reduction and Its Methodological Implicatiions - Dagys, Jonas (Problemos, 2012)
The object of this paper is the controversy about the materialist accounts of sensory qualia in analytic philosophy of recent decades. The first section deals with the identity thesis and reductionist strategy connected to it that has established and shaped the development of materialist problematics as central to philosphy of mind. The second section discusses two most influential antireductionist arguments – the knowledge argument and the argument from the conceivability of zombies. The the paper focuses on the epistemological and semantic aspects of the controversy that can be translated into the different interpretations of two-dimensional modal matrix, which allows to specify the disagreement between reductionism and antireductionism. Finally the conclusion arrived at in the last section is that the premises of antireductionist arguments are not compatible with the stable connection between mental and physiological domains, and thus contemporary philosophy of mind brings out the dilemma: either we hypostatize the introspectively available qualitative content on the basis of epistemic asymmetry of the mental and physical concepts, thereby deriving a dualist ontology, and embrace all the sceptical consequences, or we prefer the extensional explanation of concepts, without internalist ambitions, conceivability of zombies, and antireductionist conclusions.
Keywords: philosophy of mind; reductionism; knowledge argument; zombie argument; identity thesis